(untitled) (Journal of Hama University, 2025)
This study aimed to detect the prevalence of Equid herpesvirus abortion disease in these horses in Hama governorate. The study was conducted on 100 blood samples of effected horses with Equid herpesvirus abortion disease in horses flocks in Hama governorate. Results of serological diagnosis using ELISA showed that 14 samples were positive cases of 100 samples of effected horses, with total prevalence of 14%, The upper prevalence of Equid herpesvirus abortion disease in horses was in Alforosia as reported prevalence 16.67%, while prevalence of Equid herpesvirus abortion disease in horses was in Albarazia as 7.14%. Results reflect an important risk index on public veterinary health and have significant economic effects in the field of horeses breeding.